Pengaruh Teknik Role-Playing Untuk Mengurangi Dampak Konformitas Negatif Pada Remaja - Oktaliani, Gladys; Khairun, Deasy Yunika; Nurmala, Meilla Dwi (Program Studi Bimbingan dan Konseling, 2024)
Conformity is a social behavior change experienced by an individual during socialization in their environment. In the adolescent phase, teenagers often engage in conformist behavior, where they follow the rules of a large or small group to be recognized as members, even if it goes against their true selves. The purpose of this research is to examine whether there is a change in the impact of Role-Playing Technique on reducing negative conformity among adolescents at SMAN 1 Kramatwatu. The research uses a Quasi-Experimental method with an Experimental Group and a Control Group. The Pre-Test results show that out of a total of 124 students, 16 students fall into the high category, 108 students in the moderate category, and no students in the low category. Those in the high category become the experimental sample. The hypothesis test in this research uses the Mann Whitney U test, and the hypothesis test result shows an Asymp. Sig. (2-tailed) = 0.001, where the value is < 0.05. Therefore, it can be concluded that the hypothesis in this research is accepted, and H0 is rejected. Thus, it can be concluded that there is a difference in the results between the experimental group that received treatment and the control group that did not receive treatment. Due to this difference, the result can be stated that the Role-Playing Technique has an effect on reducing the negative impact of conformity among adolescents at SMAN 1 Kramatwatu.